PENGELOLAAN FASILITAS OBJEK WISATA AIR TERJUN TUJUH TINGKAT BATANG KOBAN DI KABUPATEN KUANTAN SINGINGI - Desta Afriani; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Management of Facilities the  Tourist of Air Terjun Tujuh Tingkat Batang Koban, that managed by the department of culture and tourism Kuantan Singingi regency as government agencies that are responsible for the management and development of Air Terjun Tujuh Tingkat Batang Koban.The purpose of the research is to know the management of Air TerjunTujuh Tingkat Batang Koban of Kuantan Singingi regency and the factors that influence the management ofAir Terjun Tujuh Tingkat Batang Koban of Kuantan Singingi regency. The concept of the theory is the management of according to George R. Terry, the researcher uses the method of descriptive qualitative. Kind of the data is used the primary and secondary. The data collection of the researcher is use the techniques by observation, interviews, and documentation. By using techniques purfosif as an informan for the research. The conclusion of the results of this researchthat the management of Air Terjun Tujuh Tingkat Batang Koban in Kuantan Singingi regency.it is can be seen from the facility which is already a lot a damaged and didn’t do maintenance by department of culture and touristm of kuantan singingi regency. The factors that affect the management of facilities the air terjun tujuh tingkat batang koban in Kuantan Singingi regency is human resources, budget, infrastructure and natural condition. Keywords: Management, facility, Tours Air Terjun Tujuh Tingkat Batang Koban